THE JUDICIARY IN THE PROCESS OF DEMOCRATIC BACKSLIDING: A COMPARATIVE ANALYSIS OF EASTERN EUROPEAN COUNTRIES (POLAND, HUNGARY, THE CZECH REPUBLIC, BULGARIA, SERBIA) - Revenko, Denis (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2026)
The article examines the transformation and erosion of the judiciary in five Eastern European countries – Poland, Hungary, the Czech Republic, Bulgaria, and Serbia — in the context of democratic backsliding (democratic backsliding). The independence of the judiciary is a foundational pillar of liberal democracy, serving as a critical check on executive and legislative power. Understanding how this pillar can be systematically weakened is therefore essential for assessing the resilience of democratic institutions across the region. It characterizes the key parameters of comparative analysis: the independence of the constitutional court, the independence of ordinary courts, judicial governance, and external pressure. Special attention is paid to identifying common strategies for weakening judicial authority, particularly the use of mechanisms of «autocratic legalism» and «state capture», as well as analyzing instruments of political pressure on judges — from discretionary powers of judicial administration heads to the creation of politicized disciplinary bodies. The study considers the differences between countries determined by the configuration of political power (the presence of a constitutional majority), the density of international institutional oversight, and the structure of accountability mechanisms. It is shown that Hungary and Poland experienced a targeted systemic assault on the judiciary, Bulgaria and Serbia suffer from chronic institutional erosion, while the Czech Republic serves as a counterexample of judicial resilience due to strong judicial self-governance and effective internal checks and balances. Practical recommendations for Ukraine are formulated, including the need for legislative protection of the High Council of Justice from political influence, preventing the creation of discretionary disciplinary bodies, implementing transparent mechanisms of judicial self-governance, and enhancing public trust through openness of judicial procedures. The findings can serve as an analytical framework for further reforms of Ukraine’s judicial system on its path to European integration and strengthening the rule of law in the post-war period.